Inferring the Phylogenetic Positions of Two Fig Wasp Subfamilies of Epichrysomallinae and Sycophaginae Using Transcriptomes and Mitochondrial Data - Dan Zhao; Zhaozhe Xin; Hongxia Hou; Yi Zhou; Jianxia Wang; Jinhua Xiao; Dawei Huang (Life, 2021)
Fig wasps are a group of insects (Hymenoptera: Chalcidoidea) that live in the compact syconia of fig trees (Moraceae: Ficus). Accurate classification and phylogenetic results are very important for studies of fig wasps, but the taxonomic statuses of some fig wasps, especially the non-pollinating subfamilies are difficult to determine, such as Epichrysomallinae and Sycophaginae. To resolve the taxonomic statuses of Epichrysomallinae and Sycophaginae, we obtained transcriptomes and mitochondrial genome (mitogenome) data for four species of fig wasps. These newly added data were combined with the data of 13 wasps (data on 11 fig wasp species were from our laboratory and two wasp species were download from NCBI). Based on the transcriptome and genome data, we obtained 145 single-copy orthologous (SCO) genes in 17 wasp species, and based on mitogenome data, we obtained 13 mitochondrial protein-coding genes (PCGs) for each of the 17 wasp species. Ultimately, we used 145 SCO genes, 13 mitochondrial PCGs and combined SCO genes and mitochondrial genes data to reconstruct the phylogenies of fig wasps using both maximum likelihood (ML) and Bayesian inference (BI) analyses. Our results suggest that both Epichrysomallinae and Sycophaginae are more closely related to Agaonidae with a high statistical support.